1991
DOI: 10.1017/s0950268800048536
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship between the HA genes of type A influenza viruses isolated in off-seasons and later epidemic seasons

Abstract: SUMMARYFrom January 1985 to March 1989, off-season viruses of H1N1 and H3N2 subtypes of influenza A viruses were isolated on five occasions in Japan. The HA gene sequences of the influenza A(H1N1) and A(H3N2) viruses isolated in Japan from 1985–9 were analysed and the phylogenetic tree for each subtype virus was constructed to determine any genetic relationship between viruses isolated in off-seasons and the epidemic viruses of the following influenza seasons. In one instance with H1N1 viruses in 1986 and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Ludwig et al (1991) indicated that the rate of base changes of the NS gene of H2N2 and H3N2 viruses is faster than that of the H1N1 viruses and calculated this to be 2"23 nucleotide substitutions per year for the H2N2 and H3N2 viruses. As reported previously (Nakajima et al, 1991), when we compared the HA genes of influenza viruses isolated in a short period, the rate of nucleotide substitution was different for each virus. The same concept can be applied (Elleman et al, 1982).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Ludwig et al (1991) indicated that the rate of base changes of the NS gene of H2N2 and H3N2 viruses is faster than that of the H1N1 viruses and calculated this to be 2"23 nucleotide substitutions per year for the H2N2 and H3N2 viruses. As reported previously (Nakajima et al, 1991), when we compared the HA genes of influenza viruses isolated in a short period, the rate of nucleotide substitution was different for each virus. The same concept can be applied (Elleman et al, 1982).…”
mentioning
confidence: 76%
“…Evolutionary trees of the same type or subtype of human influenza viruses were constructed mainly for the HA genes of A (H1N1) (Raymond et al, 1986;Cox et al, 1989;Nakajima et al, 1991), A (H3N2) (Both et al, 1983;Nakajima et al, 1988) and B (Yamashita et al, 1988;Kanegae et al, 1990;Rota et al, 1990Rota et al, , 1992Nakajima et aL, 1992) viruses. Buonagurio et al (1986) sequenced 15 NS genes of the H1N1, H2N2 and H3N2 subtypes of human influenza A viruses and found that the NS genes of human influenza A viruses changed linearly from 1933 to 1985 at a constant rate.…”
mentioning
confidence: 99%
“…In our previous study, we analysed the HA gene sequences of the influenza A(H3N2) and A(HIN1) viruses isolated in Japan and Southeast Asia during the period of 1985-90 in order to determine whether the viruses isolated in off-seasons are genetically related to the viruses of the following epidemics [3]. The results showed that the spring isolates were in most cases genetically close to some of the winter isolates and they were considered to be the parental viruses for the following influenza seasons.…”
Section: Introductionmentioning
confidence: 99%
“…The HA1 portion of the virus haemagglutinin, the main scene of antigenic drift, has evolved along one pathway with short side branches (Raymond et al, 1986;Cox et al, 1989;Nakajima et al, 1991 ;Kinnunen et al, 1992;Xu et al, 1993). The present antigenic variant (Taiwan/1/86-1ike viruses; Robertson, 1987;Cox et al, 1989;Rajakumar et al, 1990) appeared in 1986.…”
Section: Human Influenza a (H1n1) Viruses Reappeared In 1977mentioning
confidence: 99%
“…Fin/72/88 was consequently a 'herald strain' closely related to viruses of the following influenza season. Attention has also been given to the occurrence of herald strains in Japan (Nakajima et al, 1991 isolated in several European countries (WHO, 1988). In the autumn of 1988, the outbreak began in Europe earlier than in previous years (WHO, 1989).…”
Section: Human Influenza a (H1n1) Viruses Reappeared In 1977mentioning
confidence: 99%